Prevalence of chronic kidney disease in Sri Lanka: a profile of affected districts reliant on groundwater - Kafle, Kashi; Balasubramanya, Soumya; Horbulyk, Ted (Elsevier, 2019)
This analysis provides new estimates of chronic kidney disease (CKD) prevalence – including CKD of unknown etiology (CKDu) – across ten districts most affected by CKD in Sri Lanka, including an examination of rural households' historical reliance on groundwater consumption. A carefully designed household survey provides information on whether these households self-reported having a member in the decade prior to 2018, who had been clinically diagnosed with CKD. Households were classified according to whether or not they had used groundwater (from household wells, agro-wells or springs) as their primary source for drinking or cooking for at least five years between 1999 and 2018. More than 98% of households reported having consumed groundwater as their primary source of drinking or cooking water for at least five of those years and >15% of households reported having at least one CKD-affected member in the ten-year period up to 2018, but these numbers varied across and within districts. The reported characteristics of symptomatic individuals reveal that the incidence of CKD was significantly higher among females (62%) than males (38%). In addition to CKD, about 63% of symptomatic individuals had hypertension and about one-third of them also had diabetes. About 33% of the symptomatic individuals had neither diabetes nor hypertension, where this group most closely fits commonly used definitions of CKDu. With a survey response of over 8000 households comprising as many as 30,000 individuals, these data illustrate the scale of CKD in the most-affected districts of Sri Lanka on an aggregate basis as well as revealing differences across districts and at the sub-district level.